Intercessory prayer and the Carolingian monastic ideal, c. 750-820 - Choy, R (2012)
The establishment of a new concept of intercessory prayer, from an activity sought of the individual holy man to an occupation characterizing an entire monastic community, has recently received much attention; historians have shown that the function of intercession had become, by the Carolingian period, the pre-eminent feature of early medieval monasticism. The role of early medieval monasteries as powerhouses of prayer has encouraged scholarly attention along two particular areas of interest: intercession within the system of medieval patronage and gift exchange, and monastic ritual elaboration. Missing in the main historiographical approaches is discussion concerning the place of intercessory prayer within the monastic ideal. This study therefore asks the central question, ‘What was the relationship between the intercessory function of monasticism and the ascetic concern for moral conversion in the time of the reforms of Benedict of Aniane, c. 750-820?’ The writings of Carolingian monastic reformers demonstrate that the chief concern of the monk was to seek and find perfection in God; it is the argument of this study that the elaborate liturgical intercession which characterized early medieval monasticism was coherent with this goal. The Introduction sets out to establish the continuity of the ascetic pursuit in the Carolingian monastic ideal with earlier monasticism. We then order our investigation by: i) proposing that monastic liturgical organization was meant to address the fundamental problem of human sin which impedes fruitful prayer, and that the additions of intercessory liturgy made by Benedict of Aniane should be seen as part of his pastoral concern for the holiness of monks (Chapter 1); ii) situating the specific intercessory performances of monastic communities – namely, the intercessory Mass and the Divine Office – within Carolingian monastic theology (Chapters 2 and 3); iii) examining how the prayer directed toward two groups of beneficiaries of intercession – fellow monks and rulers – was grounded on the the ascetic goals of moral conversion and pilgrimage toward the celestial kingdom (Chapters 4 and 5); and iv) addressing the question of what role Carolingian monastics meant for their intercessory prayers to play in society at large, and the extent to which general social concern was a priority in monastic intercession (Chapter 6). This study provides a detailed description of the ascetic ideal required for understanding the formalized ritual and patronized prayer of monasteries within its proper sphere of monastic spirituality. I conclude in particular that the increasing importance of monastic intercession was related to a heightened emphasis in Carolingian spiritual thought on the teleological theme of transformation both individual and cosmic. The intercessory function of early medieval monasticism suggests an incorporation of the spiritual pilgrimage of the wider world into the monk’s own individual discipline, and tied the monk’s ascesis to the larger story of the conversion of the world to God.